2012
DOI: 10.1073/pnas.1202910109
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Epstein–Barr virus in a gastric carcinoma cell line induces anchorage independence and global changes in gene expression

Abstract: Latent infection of EBV is linked to the development of multiple cancers that have distinct patterns of expression of viral proteins and microRNAs (miRNAs). In this study, we show that in vitro infection of a gastric epithelial cell line with EBV alters growth properties and induces growth in soft agar. The infected cells have high levels of expression of a large cluster of viral miRNAs, [the BamHI A rightward transcript (BART) miRNAs] and limited viral protein expression. Expression profile microarray analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 39 publications
(45 reference statements)
6
98
0
Order By: Relevance
“…However, these tumors are clonally infected with EBV, suggesting that EBV infection is an early event in the formation of the tumors (3). Consistent with these observations, EBV infection of an epithelial cell line in vitro is capable of promoting growth in soft agar independent of any latent protein expression (4). EBV epithelial malignancies, nasopharyngeal and gastric carcinomas, exhibit a unique expression pattern that includes extensive transcription from the BamHI A region of the viral genome (5).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…However, these tumors are clonally infected with EBV, suggesting that EBV infection is an early event in the formation of the tumors (3). Consistent with these observations, EBV infection of an epithelial cell line in vitro is capable of promoting growth in soft agar independent of any latent protein expression (4). EBV epithelial malignancies, nasopharyngeal and gastric carcinomas, exhibit a unique expression pattern that includes extensive transcription from the BamHI A region of the viral genome (5).…”
supporting
confidence: 64%
“…Importantly, EBV infection of AGS cells consistently induces anchorage-independent growth and increased motility (4,15,16). Gene expression microarray analysis of a single AGS-EBV cell line compared to parental cells suggested that there are widespread changes in host transcription due to latent EBV infection and that the downregulated genes were highly enriched for BART miRNA targets (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This subset of gastric carcinoma, 8 to 10% of cases, is more prevalent in Caucasian and Hispanic patients than Asians, and it shows no association with Helicobacter pylori infection (22). In these cases, EBV appears to play a direct oncogenic role through genome-wide alteration of promoter methylation (24), microRNA (miRNA) expression, and expression of genes involved in cell motility and transformation pathways (25). The integration status of EBV in gastric carcinoma remains poorly understood.…”
mentioning
confidence: 99%
“…In our study, we used the 2-DE approach coupled with MS to study the differentially expressed proteins of gastric epithelial AGS cell, with and without EBV infection. The same system has previously been used to analyze differences in gene expression using cDNA microarrays (Marquitz et al, 2012). In the current study, we obtained an overview of the altered protein expressions of host cells responding to EBV infection.…”
Section: Discussionmentioning
confidence: 99%